OBJECTIVE AND SUBJECTIVE FACTORS OF MEDICAL DRUG CHOICE - E. B. Babanskaya; L. V. Menshikova (Столичная издательская компания, 2017)
Aim. To analyze the factors of medical choice in the prescription of medicinal drug (MD) for the treatment of cardiovascular diseases. Material and methods. A questionnaire survey of 212 doctors (138 physicians and 42 general practitioners) was performed in Irkutsk region and Republic of Buryatia. Questions were related to the physicians' choice of the original or generic MD and the factors that influence this choice. Results. The majority of respondents prefer the foreign MD, while they prescribed both original and generic drugs (60.4%). The determining factor in the prescription of MD is its efficacy (91.5-95.3%). The main source of information of MD for physicians is the medical literature (78.3%). Only 23.6% of doctors choose the MD based on the results of clinical trials and information about it in specialized medical literature. A half of the respondents believe that their knowledge of cardiovascular MD is insufficient. Doctors need and are interested in information on the pharmacokinetics and pharmacodynamics of MD, side effects, drug interactions and results of clinical studies. Conclusion. It is necessary to focus on the clinical pharmacology of cardiovascular MD during the training of doctors in specialized courses of continuous medical education.